Synopsis, Diet transformation in Ethiopia - Worku, Ibrahim; Dereje, Mekdim; Minten, Bart (International Food Policy Research Institute, 2015)
Ethiopia’s food economy is transforming fast. To better understand this ongoing process, we analyze changes in food consumption that have happened over the period between 1996 and 2011, relying on four rounds of nationally representative household data. The main findings are as follows: First, the share of food in overall expenditures is declining. Second, quantities consumed per capita are increasing. Third, the relative importance of cereals is on the decline. Fourth, there are large differences in the cereal basket of households between rural and urban areas, indicating the importance of increasing urbanization on the food economy. Fifth, cereals – and in particular maize – remain the largest source of calories in the food basket. Sixth, there is a relative shift in consumption to more expensive foods. Seventh, purchased foods are seemingly becoming more important. Finally, there are strong differences in food consumption by income level, but all levels exhibit changes over time. This diet transformation has important implications for the food security debate and for agricultural and food policy in the country.